Structure and expression of murine germ-line immunoglobulin epsilon heavy chain transcripts induced by interleukin 4. - Gerondakis, S (1990)
The murine lymphokine, interleukin 4 (IL-4) is able to specifically promote isotype switching to IgG1 and IgE in cultures of mitogen-stimulated B cells. Emerging evidence suggests that germ-line immunoglobulin heavy chain gene transcription may direct switching by modulating switch-region accessibility to a recombinase. In this study, cloned cDNA copies of the germ-line epsilon heavy chain transcript have been used to determine the genomic organization of this transcription unit. The 5' end of these transcripts are derived from an exon, denoted I epsilon, located 2 kilobases 5' of the C epsilon switch region [C epsilon = epsilon heavy chain constant (C) region gene]. Nucleotide sequence analysis reveals that this RNA does not encode a protein, as the I epsilon exon contains termination codons in all reading frames. Germ-line epsilon chain transcripts can be detected in cultures of normal splenic B cells treated with IL-4 within 24 hr, and this expression correlates with subsequent switching to C epsilon. Consistent with the IL-4 inducibility of this RNA is the identification of a motif upstream from the site of transcription initiation that closely resembles a transcription element implicated in the IL-4 regulation of the gene encoding the murine class II histocompatibility antigen, A alpha k. These data lend support to the accessibility model of isotype switching and implicate IL-4 in the transcriptional activation of the C epsilon locus.